Impact of Privatization of Ports on Relative Efficiency of Major Ports of India. (August 2016) - Dasgupta, Mrinal Kumar; Sinha, Deepankar
In this article, an attempt has been made to identify the effect of liberalization on the efficiencies of container terminals of major ports of India. In India, the liberalization process started since 1991. As a result, many of the major ports, administered by the union government of India privatized their container terminals. In this study, the efficiency of privately managed terminals, under major ports, has been compared with public container terminals using data envelopment analysis (DEA). In this article, output-oriented DEA using DEAP (Data Envelopment Analysis (Computer) Programme) software has been carried out where the inverse of turnaround time per thousand twenty equivalent units (TEUs) has been taken as the output. The results of the study show that though the efficiency of containers terminals are affected by privatization to a great extent, they depend on other factors too.